Kombinasi Proximal Sciatic Nerve Nerve Block Dan Lumbar Plexus Block Single Shot Pada Operasi Amputasi Above Knee Dengan Gangguan Fungsi Kardiak - Wardhana, Wisnu; Suranadi, I Wayan (Syntax Corporation, 2025)
Peripheral nerve blocks are crucial regional anesthesia techniques, particularly for patients with cardiac dysfunction who are at high risk for general anesthesia. This study aims to describe the effectiveness of combining proximal sciatic nerve block and single-shot lumbar plexus block as an anesthetic method for above-knee amputation procedures in patients with compromised cardiac function. This combination technique seeks to provide optimal pain control while minimizing hemodynamic instability often associated with general anesthesia. This is a case report involving a patient with a history of cardiac disease undergoing above-knee lower limb amputation. The results indicate that the combined block technique provided adequate anesthesia throughout the procedure, maintained hemodynamic stability, and ensured faster and safer postoperative recovery. This approach is recommended as a safe and effective anesthetic alternative for high-risk patients with cardiac dysfunction.